International language monism and homogenisation of journalism - Meyer, Gitte (Javnost (Ljubljana), 2008)
Different languages representing different frameworks of thought and perspectives on reality also carry different frameworks of thought on journalism and on how the profession may contribute to democracy. A shortcut to understanding varieties of journalism may be provided by the study of diff erent understandings of journalistic key notions in diff erent languages, by comparing two varieties of journalism - the "reporter" and the "publicist" tradition - in English and German. The current homogenisation of journalism, using the Anglo-American reporter traditions as the model, strengthened by the simultaneous move towards English as the international language, may be seen as a loss of diversity in journalism and even a threat to democratic diversity in Europe. An increased stress on language understanding and conceptual hygiene in the education of journalists is proposed to maintain diversity.
Keywords: Europe; Evropa; večkulturnost; democracy; demokracija; mass media; množični mediji; novinarstvo; journalism; informiranje; obveščanje; objektivnost; jeziki; knowledge; znanje; jezikovna kultura